2022
DOI: 10.1002/smll.202205088
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Anti‐Solvent Treatment for Efficient 2D Dion–Jacobson Perovskite Solar Cells

Abstract: inherent instability of halide perovskite when it is exposed to the ambient environment, such as heat, [5] light, [6] and humidity, [7] becomes a major obstacle for its commercial applications. The 2D perovskites exhibit improved stability due to the introduction of hydrophobic bulky organic cations, [8,9] but the PCE of 2D PSCs is much lower than the 3D PSCs. [10] Enhanced crystallinity quality and reduced trap density are beneficial to improve the performance of 2D PSCs. It is noteworthy that the one-step sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Moreover, a secondary anti-solvent method was reported by Zhang and co-workers for further passivating surface defects. 105 Fig. 15f shows a schematic diagram of the common and secondary anti- solvent processes for (BDA)(MA 0.07 FA 0.93 ) 4 Pb 5 I 16 perovskite preparation.…”
Section: Surface/interface Modificationmentioning
confidence: 99%
“…Moreover, a secondary anti-solvent method was reported by Zhang and co-workers for further passivating surface defects. 105 Fig. 15f shows a schematic diagram of the common and secondary anti- solvent processes for (BDA)(MA 0.07 FA 0.93 ) 4 Pb 5 I 16 perovskite preparation.…”
Section: Surface/interface Modificationmentioning
confidence: 99%
“…Despite better stability, the efficiencies of the quasi-2D PSCs are still lower than those of the 3D ones. To solve this issue, some methods have been adopted, such as additive engineering, hot casting, and post-treatment of the perovskite. In these methods, post-treatment of the perovskite is an effective method to enhance the performance and stability of quasi-2D PSCs. Jin et al adopted a sequential post-treatment method to fabricate quasi-2D ACI-phase PSCs, where guanidinium thiocyanate (GASCN) and methylammonium chloride (MACl) were used as post-treatment reagents, leading to a high PCE of 15.27%.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this issue, some methods have been adopted, such as additive engineering, hot casting, and post-treatment of the perovskite. In these methods, post-treatment of the perovskite is an effective method to enhance the performance and stability of quasi-2D PSCs. Jin et al adopted a sequential post-treatment method to fabricate quasi-2D ACI-phase PSCs, where guanidinium thiocyanate (GASCN) and methylammonium chloride (MACl) were used as post-treatment reagents, leading to a high PCE of 15.27%. Zhang and Park applied post-treatment to quasi-2D ACI-phase PSCs, where amphoteric imidazolium iodide (ImI) was used as a post-treatment reagent; thus, a high efficiency over 22% was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary anti-solvent strategy for DJ quasi-2D perovskite films was proposed by Zhang et al The surface defect density was significantly reduced based on conventional surface passivation, which paved another route to further improve the efficiency of PSCs. 17 by Chen and co-workers, which could effectively improve defect passivation and charge transport. 18 However, the reported investigation on DJ quasi-2D PSCs mostly focuses on the surface modification of perovskite-active layers, while the study about the underlying surface (interface at the CTL/perovskite) is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The device with interfacial modification achieved an improved PCE from 13.78 to 16.75%, which was mainly attributed to the suppression of bulk and interfacial defects. A secondary anti-solvent strategy for DJ quasi-2D perovskite films was proposed by Zhang et al The surface defect density was significantly reduced based on conventional surface passivation, which paved another route to further improve the efficiency of PSCs . A modified interface at the DJ-phase perovskite/charge transporting layer (CTL) through a novel annealing process of perovskite films was demonstrated by Chen and co-workers, which could effectively improve defect passivation and charge transport …”
Section: Introductionmentioning
confidence: 99%